Sustainability and Reproduction: A Human Rights Based Approach/Nachhaltigkeit and Fortpflanzung, ed/hg Muller S., Morciniec Jan P. Interdisciplinary Sustainability. Stimuli for Further Reflection/Interdisziplinar Nachaltigkeit. Anregunden zum Weiderdeneken - Ignovska Elena (Facultas, 2023)
The paper approaches sustainability from a human rights perspective. It takes anthropocentric lenses towards environmental issues, arguing that humans and the environment and interconnected and therefore interdependent. The ECtHR’s contribution has proven revolutionary by broadening the scope of certain rights stipulated in the ECHR to the area of environmental protection. On the other hand, even national courts could apply the human rights approach on national level before it even reaches the ECtHR. Family law issues are at the borderline between private and public law. In the intersection of sustainability, environment and families there is the intersection of reproduction. Sustainable development is vulnerable because most people, families, and governments care more about their own sustainability than about the whole world. The paper uses the same human rights approach to answer how to solve reproductive discrepancies (overpopulation and below-replacement fertility rates) in different regions that threaten planetary sustainability in different ways.
Bioethics in Discussion 5 ed/hg Muller S., Morciniec Jan P. Interdisciplinary Sustainability. Stimuli for Further Reflection/Interdisziplinar Nachaltigkeit. Anregunden zum Weiderdeneken
Keywords: Sustainability; reproduction; family; human rights approach